Intelligent vehicular networks and communications : fundamentals, architectures and solutions - Paul, Anand J.; Chilamkurti, Naveen, 1974-; Daniel, Alfred; Rho, Seungmin; ScienceDirect eBooks (Amsterdam ; Boston : Elsevier/AP, Academic Press is an imprint of Elsevier, 2017)
"Intelligent Vehicular Network and Communications begins with how the transportation system has transformed into today's Intelligent Transportation System (ITS). It explores the design goals, challenges, and frameworks for modeling an ITS network, discussing vehicular network model technologies, mobility management architectures, and routing mechanisms and protocols. It looks at the Internet of Vehicles, the vehicular cloud, and vehicular network security and privacy issues. The book investigates cooperative vehicular systems, a promising solution for addressing current and future traffic safety needs, and high mobility. Intelligent Vehicular Network and Communications examines experimental work in such areas as Controller Area Network protocol and working function of On Board Unit, as well as working principles of roadside unit and other infrastructural nodes. The book examines big data in vehicular networks, exploring various business models, application scenarios, and real-time analytics. This book concludes with a look at autonomous vehicles."--
Chapter 1. Introduction : intelligent vehicular communications -- Chapter 2. Intelligent transportation systems -- Chapter 3. Vehicular network (VN) model -- Chapter 4. Evaluation of vehicular network models -- Chapter 5. Cognitive radio in vehicular network -- Chapter 6. Theory and application of vehicular networks -- Chapter 7. Vehicular network as business model in Big Data -- Chapter 8. Big Data collision analysis framework -- Chapter 9. Future trends and challenges in ITS.
Print version record.
Includes bibliographical references and index.
Elsevier
Keywords: Vehicular ad hoc networks (Computer networks); Intelligent transportation systems; Big data; Intelligent transportation systems; Big data; Vehicular ad hoc networks (Computer networks); BUSINESS & ECONOMICS / Industries / Transportation; TRANSPORTATION / Public Transportation; Electronic books